Delayed flowering due to 'cold memory' is regulated by suppression of FLOWERING LOCUS T-like 3 gene in chrysanthemums - Sumitomo, Katsuhiko; Nakano, Yoshihiro; Hisamatsu, Tamotsu; Oda, Atsushi; Narumi-Kawasaki, Takako; Fukai, Seiichi; Higuchi, Yohei (The journal of horticultural science & biotechnology, 2023)
Chrysanthemum (Chrysanthemum morifolium) is a short-day (SD) plant native to the temperate zone. SD and warm conditions suitable for flowering occur in both spring and autumn. When chrysanthemum plants are exposed to prolonged low temperatures, they are unable to induce flowering for a time afterwards. Therefore, chrysanthemums do not flower in spring, because they are in a state of internal suppression of flowering due to low temperatures in winter (i.e., 'cold memory'). To elucidate the mechanism of the floral suppression by cold memory, we analysed the expression of FLOWERING LOCUS T-like 3 (CsFTL3), which encodes a floral promoter in the wild C. seticuspe. SD induced CsFTL3 upregulation and flowering in untreated plants, but this induction was suppressed in plants with 12-weeks' cold treatment. Cold memory had little effect on flowering in CsFTL3-overexpressing plants. These results indicate that cold memory suppresses flowering by repressing CsFTL3. This prevents floral induction under SD in spring, and is one of the factors that determines the autumn-flowering nature of chrysanthemum.